2015
DOI: 10.1182/blood-2015-04-641142
|View full text |Cite
|
Sign up to set email alerts
|

A novel mechanism for NETosis provides antimicrobial defense at the oral mucosa

Abstract: Key Points Saliva induces bactericidal and DNase resistant NETs in the oral cavity via sialyl LewisX- L-selectin signaling. Disordered homeostasis in the oral cavity may lead to deficient saliva-mediated NETosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 41 publications
2
75
0
1
Order By: Relevance
“…Dissolution of NETs by DNase, long after the NET-exposed bacteria had officially been declared dead, allowed revival of the NET-associated microbes (57). Indeed, we found that bacteria bound to PMA-induced NETs are alive, as determined by live/dead staining (18). The report of a patient with chronic granulomatous disease (CGD) and Aspergillus infection who was rescued by gene therapy that restored the capacity to mount a respiratory burst and generate NETs has been considered proof of principle of the role of NETs in immune defense (58).…”
Section: Are Nets Important For Immune Defense?mentioning
confidence: 72%
See 3 more Smart Citations
“…Dissolution of NETs by DNase, long after the NET-exposed bacteria had officially been declared dead, allowed revival of the NET-associated microbes (57). Indeed, we found that bacteria bound to PMA-induced NETs are alive, as determined by live/dead staining (18). The report of a patient with chronic granulomatous disease (CGD) and Aspergillus infection who was rescued by gene therapy that restored the capacity to mount a respiratory burst and generate NETs has been considered proof of principle of the role of NETs in immune defense (58).…”
Section: Are Nets Important For Immune Defense?mentioning
confidence: 72%
“…Chemokine receptors are necessary for integrin activation and signaling (10,17). Integrins generate signals that elicit NETosis in response to bacteria, and NETs are not produced when integrins are deficient, such as in leukocyte adhesion deficiency (18). l-Selectinmediated signaling was recently demonstrated to elicit NETs in vitro (18).…”
Section: Inducers Of Net Formationmentioning
confidence: 99%
See 2 more Smart Citations
“…In vivo observation of neutrophils revealed their presence in the dental plaque and that NET formation is detected in the oral biofilm, the saliva, and also the crevicular exudate (155,197,(380)(381)(382). Due to the large quantity of bacteria present dispersed throughout the gingival crevice, phagocytosis is an ineffective means for bacterial control, therefore NETs could serve as a more effective strategy for neutrophils to respond to infection (197).…”
Section: Discussionmentioning
confidence: 99%